2015
DOI: 10.1002/ijc.29428
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced localization of IL-12-expressing mesenchymal stem cells to enhance the curative effect in murine metastatic hepatoma

Abstract: Irradiation in conjunction with gene therapy is considered for efficient cancer treatment. Mesenchymal stem cells (MSCs), due to their irradiation-promotable tumor tropism, are ideal delivery vehicles for gene therapy. In this study, we investigated whether treatment with radiation and interleukin (IL)-12-expressing MSCs (MSCs/IL-12) exerts improved antitumor effects on murine metastatic hepatoma. HCa-I and Hepa 1-6 cells were utilized to generate heterotopic murine hepatoma models. Tumor-bearing mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Besides being part of the GBM microenvironment [28], MSCs have been suggested as therapeutic vectors for cellular therapy of GBM [2330], but such treatment is still not approved due to observed opposite effects of MSCs on the same type of tumors in vivo and in vitro [28, 38]. However, here we show for the first time that the reason for the opposite effect is also the heterogeneity of GBM cells, highly relevant for an overall response of infiltrated and/or exogenously applied MSCs into the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being part of the GBM microenvironment [28], MSCs have been suggested as therapeutic vectors for cellular therapy of GBM [2330], but such treatment is still not approved due to observed opposite effects of MSCs on the same type of tumors in vivo and in vitro [28, 38]. However, here we show for the first time that the reason for the opposite effect is also the heterogeneity of GBM cells, highly relevant for an overall response of infiltrated and/or exogenously applied MSCs into the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are increasingly used in cell therapies and tissue engineering because of their availability, multi-potency, and immunomodulatory activity [22]. Recruited bone marrow-derived MSCs can home neoplasia and become part of the tumor microenvironment [2326], including GBM [27], but seem to have dual roles in tumors, which mainly depend on their immuno-activation status [28]. In glioma, both roles of MSCs in promotion [24, 26] and inhibition of tumor growth have been reported [2630].…”
Section: Introductionmentioning
confidence: 99%
“…Balyasnika et al , showed TRAIL expressing MSCs in combination with irradiation promoted survival rate in brain tumor bearing mice42. More recently, it has been shown that irradiation enhanced curative effects of IL-12 expressing MSCs in murine metastatic hepatoma by inducing MSCs localization and increasing apoptotic activity43. Radiotherapy enhanced tumor cell sensitivity to TRAIL by inducing expression of DR-4/DR-5 in human or DR-5 in mice confirmed in wide range of tumor such as lung, colon, head and neck, prostate and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These include modification to produce immunostimulatory cytokines (e.g. IFN-α, IFN-β, IL-12) and T cell trafficking molecules such as LIGHT [50][51][52][53].…”
Section: Strategies To Counteract Adaptive Resistance To Immune Checkmentioning
confidence: 99%